The How of Toponymy: A Comment on Tent's "Approaches to Research in Toponymy". (December 2015) - Nash, Joshua
Abstract : A comment which considers several ways the how of toponymy is an addendum to Tent's (2015) where, who, when, what, and why of toponymic research. Summarizing Tent's claims leads to listing and identifying less–mainstream yet theoretically pertinent research concerns central to the how of toponymics.